IMPLEMENTASI ALTERNATIVE DISPUTE RESOLUTION (ADR) DALAM PENYELESAIAN SENGKETA WARIS DI DESA BEJI KEDUNGBANTENG - Fatorina, Fetri; Abdurrahman, Fahmi (Faculty of Social, Economics and Humanities, 2024)
In Indonesia, inheritance law consists of Islamic inheritance law, western civil inheritance law, and customary inheritance law. Dispute resolution is generally divided into two, namely litigation dispute resolution and non-litigation channels. Generally, inheritance disputes are resolved through litigation. In contrast to Beji village, inheritance dispute resolution can be done through non-litigation channels. This research aims to find out how alternative dispute resolution is implemented in resolving inheritance disputes in Beji Kedungbanteng Village. This type of research was field research using a normative-empirical approach. The data collection techniques used in this research were observation and documentation. The research results state that Alternative Dispute Resolution (ADR) is a non-litigation dispute resolution solution. The application of ADR in resolving inheritance disputes starts from consultation, negotiation and mediation. Consultations are carried out by the disputing parties with religious leaders or local community leaders. After consultation, negotiations are then carried out with the parties to the dispute. If negotiations are unsuccessful then mediation is carried out. Mediators in resolving inheritance disputes in Beji Village are religious leaders, community leaders, or the village government. If mediation is unsuccessful, the dispute will be resolved through litigation.